1993
DOI: 10.1086/ntj41789041
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Tax Preparer Usage: Evidence From Panel Data

Abstract: This study provides new evidence on the factors associated with using tax return preparers from a balanced panel of microlevel tax return data for 1982-4. The results of fixed-effects logit models that control for unobservable differences levels of paid-prepared and self-prepared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…In the literature review carried out in this study, most of the earlier empirical studies were found to support the results of the present study, such as the studies by Clotfelter (1983), Feinstein (1991, Christian et al (1993), Joulfaian and Rider (1998), Ali et al (2001), Lin and Yang (2001), McGee and Ho (2006), Lingle (2006), andRossi (2006). Hai and See (2011) found that the high tax rate led to high tax non-compliance, and Park and Hyun (2003) found that increasing tax rates encouraged non-compliance behaviour.…”
Section: Discussion Of the Resultssupporting
confidence: 85%
“…In the literature review carried out in this study, most of the earlier empirical studies were found to support the results of the present study, such as the studies by Clotfelter (1983), Feinstein (1991, Christian et al (1993), Joulfaian and Rider (1998), Ali et al (2001), Lin and Yang (2001), McGee and Ho (2006), Lingle (2006), andRossi (2006). Hai and See (2011) found that the high tax rate led to high tax non-compliance, and Park and Hyun (2003) found that increasing tax rates encouraged non-compliance behaviour.…”
Section: Discussion Of the Resultssupporting
confidence: 85%
“…Further, they state that taxpayers with children are more curious about saving time and money during their tax-preparing services, compared to those taxpayers without children. Hence, Stephenson et al [ 26 ] support the propositions of time-cost-savings being relevant for the intention to use tax-preparation services stated by Christian et al [ 22 ]. According to Stephenson et al [ 26 ], future studies should also consider the size of the tax-preparation service, as small and regional tax-preparation services tend to be more taxpayer-focused than larger ones in non-regional areas are.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…Tax-preparation services utilize professional service providers, and recommendations are mandatory for their success [ 4 , 5 , 7 , 9 , 20 ], as are quality labels [ 3 , 11 ]. According to principal–agent theory, principals (i.e., taxpayers in the context of this study) hire agents (i.e., tax-preparation services) [ 10 , 13 , 21 ] because they want to complete tasks that they cannot, for many reasons (e.g., limited time, insufficient knowledge, high costs), complete by themselves [ 6 , 10 , [22] , [23] , [24] , [25] , [26] ]. Therefore, agents promise that the tasks in question will be completed adequately [ 13 ].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations